Respuestas

2012-10-18T06:12:49+02:00

A = K – l / 3                                                                                  S  =  K *  v2 / 2

A + L /3  =  K                                                                                     S

                                                                                                    ======  =   K

                                                                                                       v2 / 2

 

  X  =  y  - Z / 2                                                                                2 S /  V2  =  K

 

       2 Y – Z

 X =  ======

             2                                                                                     L  =   A * (  K  -  S  )

                                                                                               L  =  ( A * k ) – ( A * S  )

2 X  = 2 Y – Z                                                                               L  +  ( A * S )  =  A * K

2 X -  2 Y  = - Z   toda  la  ecuación   por -1

 -2X  + 2 y  = z                                                                             L  +  ( A * S )   

                                                                                                    ===========  =  K

                                                                                                                A                              

  • Usuario de Brainly
2012-10-18T06:35:04+02:00

A= K-L/3

3A=K-L

3A+L=K

 

 

X=Y-Z/2

2Y=Y-Z

2Y-Y=-Z (-1)

-2Y+Y=Z

 

 

S=KV2/2

2S=KV2

2S/V2=K

 

L=A(K-5)-PK

L=AK-5A-PK

L= (A-5)-PK

L+P/A-5=K-K

 

 

CREO QUE ES ASI